2017
DOI: 10.1200/jco.2017.35.18_suppl.lba3001
|View full text |Cite
|
Sign up to set email alerts
|

Durable remissions with BCMA-specific chimeric antigen receptor (CAR)-modified T cells in patients with refractory/relapsed multiple myeloma.

Abstract: LBA3001 Background: Chimeric antigen receptor engineered T cell (CAR-T) is a novel immunotherapeutic approach for cancer treatment and has been clinically validated in the treatment of acute lymphoblastic leukemia (ALL). Here we report an encouraging breakthrough of treating multiple myeloma (MM) using a CAR-T designated LCAR-B38M CAR-T, which targets principally BCMA. Methods: A single arm clinical trial was conducted to assess safety and efficacy of this approach. A total of 19 patients with refractory/rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 0 publications
0
52
0
Order By: Relevance
“…BCMA is a normal plasma cells marker, falls in to the near-ideal antigen for multiple myeloma with no evidence of expression on the normal non-hematological tissue [144]. Latest multi-center BCMA-CAR trials results indicate a relatively safe profile (although cytokine release syndrome -CRS and transient neurotoxicity were observed) with an overall response rate over 90% [145,146]. Other antigens currently being targeted to treat hematological malignancies include CD20 for NHL, CD138 for MM [144], CD33 [147], CD123 for AML [148,149] and CD7 for certain leukemias and lymphomas [150].…”
Section: Beyond Cd19: New Car-t Cells For Solid Tumors -In Search Of mentioning
confidence: 96%
“…BCMA is a normal plasma cells marker, falls in to the near-ideal antigen for multiple myeloma with no evidence of expression on the normal non-hematological tissue [144]. Latest multi-center BCMA-CAR trials results indicate a relatively safe profile (although cytokine release syndrome -CRS and transient neurotoxicity were observed) with an overall response rate over 90% [145,146]. Other antigens currently being targeted to treat hematological malignancies include CD20 for NHL, CD138 for MM [144], CD33 [147], CD123 for AML [148,149] and CD7 for certain leukemias and lymphomas [150].…”
Section: Beyond Cd19: New Car-t Cells For Solid Tumors -In Search Of mentioning
confidence: 96%
“…In addition, Fan et al presented the results of the LEGEND-2 study, which included 22 patients infused with the anti-BCMA LCAR-B38 M CAR product. An ORR of 100% was achieved with 63% of patients going into MRD-negative CR by flow cytometry [25]. These promising results are to be confirmed in larger numbers and with extended follow-up.…”
Section: Multiple Myeloma (Mm) and Myeloid Malignanciesmentioning
confidence: 87%
“…Indeed, severe CRS occurred in only 14% of the patients included in the LEGEND-2 trial [25]. In another study (CRB-401), Grade 1-2 CRS was reported in 73% treated patients.…”
Section: Cytokine Release Syndrome (Crs)mentioning
confidence: 95%
“…Encouragingly, the CAR principle was also successfully used to target other antigens in liquid tumor patients, such as anti-CD20 CAR T cells in refractory advanced DLBCL and refractory B-cell non-Hodgkin lymphoma patients (ClinicalTrials.gov study NCT01735604), 31,32 anti-CD22 CAR T cells to treat B-ALL patients, 33 anti-CD138 CAR T cells in multiple myeloma patients (ClinicalTrials.gov study NCT01886976), 34 and in two early-phase clinical trials targeting BCMA in multiple myeloma in the United States (ClinicalTrials.gov study NCT02658929) 35,36 and China. 37,38 Noteworthy, the FDA granted Breakthrough Designation for anti-BCMA CAR T-cell therapy in multiple myeloma. 39 CAR T-cell therapies are also being tested in various solid tumors, but this setting may present additional challenges not faced in the treatment of liquid tumors.…”
Section: Car T Cells In the Clinicmentioning
confidence: 99%